Highly effective separation of semiconducting carbon nanotubes verified via short-channel devices fabricated using dip-pen nanolithography - Park, S; Lee, H; Wang, H; Selvarasah, S; Dokmeci, MR; Park, Y; Cha, S; Kim, J; Bao, Z (2012)
We have verified a highly effective separation of semiconducting single-walled carbon nanotubes (sc-SWNTs) via statistical analysis of short-channel devices fabricated using multipen dip-pen nanolithography. Our SWNT separation technique utilizes a polymer (rr-P3DDT) that selectively interacts with and disperses sc-SWNTs. Our devices had channel lengths on the order of 300-500 nm, with an average of about 3 SWNTs that directly connected the source-drain electrodes. A total of 140 SWNTs were characterized, through which we have observed that all of the SWNTs exhibited semiconducting behavior with an average on/off current ratio of ∼10 6. Additionally, we have characterized 50 SWNTs after the removal of rr-P3DDT, through which we have again observed semiconducting behavior for all of the SWNTs with similar electrical characteristics. The relatively low average on-conductance of 0.0796 μS was attributed to the distribution of small diameter SWNTs in our system and due to the non-ohmic Au contacts on SWNTs. The largely positive threshold voltages were shifted toward zero after vacuum annealing, indicating that the SWNTs were doped in air. To the best of our knowledge, this is the first time numerous SWNTs were electrically characterized using short-channel devices, through which all of the measured SWNTs were determined to be semiconducting. Hence, our semiconducting single-walled carbon nanotube sorting system holds a great deal of promise in bringing forth a variety of practical applications in SWNT electronics. © 2012 American Chemical Society.